EVALUASI PERHITUNGAN KOS ORGANISASI SEKTOR PUBLIK (STUDI PADA SMK BISNIS DAN TEKNOLOGI BEKASI) - Nursetiani, Andini (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2019)
School is a place of education that belongs to the public sector organization and are not established with the sole purpose of seeking profit. Its true purpose is as an educational service and manifestation to achieve one of Indonesia’s goals which is stated in the Preambule of UUD 1945, namely to educate the citizens of the nation. The aim of this research is to analyze how school determine tuition unit cost for its students, to identify unit cost for education using ABC method and to evaluate the comparison between them. This research took place at SMK Bisnis dan Teknologi Bekasi.SMK Bisnis dan Teknologi Bekasi has three study programs such as Teknik dan Bisnis Sepeda Motor (TBSM), Bisnis Daring dan Pemasaran (BDPM) serta Perbankan dan Keuangan Mikro (PBKM). This research focused on the evaluation of unit cost measurement then compare it with ABC method.The result shows that SMK Bisnis dan Teknologi Bekasi implemented conventional method using previous year’s base rate and this method caused less accurate in determining unit cost which every student need to bear. This research can be one of the recommendation on determining school unit cost for upcoming year.